From teacher to trainer - Ellman, Matthew T.; Lucantoni, Peter (Cambridge professional learning, 2023)
'From Teacher to Trainer' helps new trainers and experienced teachers to develop the knowledge and skills they need to successfully train and develop language teachers, including teachers of English. It combines theory with practical guidance to explore a range of techniques and strategies that can be applied in any training context